Pengembangan Bahan Ajar Ungkapan Maaf dan Terima Kasih Berbasis Permainan Tradisional Batun Bageq - Rohana Safitri; Syaiful Musaddat; Johan Mahyudi (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This study aimed to improve the ability of first-grade elementary school students to express apology and gratitude through the development of a lesson based on the traditional Indonesian game, Batun Bageq. Batun Bageq, a popular game in Indonesia, was used as a medium to enhance students' communication skills. The developed lesson included materials, methods, and media tailored to the needs and characteristics of first-grade students. The results showed that the game-based lesson significantly improved students' ability to express apology and gratitude in a more effective and interactive manner. Therefore, this lesson can serve as an effective alternative for enhancing students' communication skills in first-grade elementary school settings